Evaluation of immune booster formulation by traditional health practitioners: Phytochemical, antioxidant and mineral elements studies (Funded work) - KHUMALO. B. M; QWEBANI-OGUNLEYE. T; EJIDIKE. I. P; MTUNZI. F. M; PINKOANE. M (International Journal of Pharma and Bio Sciences, 2018)
In recent times, the utilisation of medicinal plants for their immune boosting potential have been preferred over pharmaceutical drugs due to their low toxicity and costs. A herbal immune booster was formulated by the traditional health practitioners (THPs) from the Vaal Region, South Africa for immune health development. This study is aimed at evaluating the phytochemicals and the mineral elements in this immune booster formulation. The elemental analysis was conducted using atomic absorption spectrophotometer. The phytochemicals screening of the immune booster revealed that the formation contained alkaloids, flavonoids, phenols and saponins while steroids, tannins and glycosides were absent. Immune booster formulation showed a good antioxidant activity for ABTS radical (IC50 = 0.026 ± 0.021 mg/mL) than for DPPH radical (IC50 = 0.191 ± 0.025 mg/mL). The mineral studies showed that the immune booster possesses a significant amount of Fe (14.7328 ±2.01 ppm), Na (8.6633 ±1.81 ppm) and Mg (5.3083 ±0.88 ppm). The calcium content was found to be 1.3466 ±0.31 ppm and Co, Cu and Zn were all less than 1.00 ppm whilst Pb was 1.2146 ±0.07 ppm and K was absent. The high concentration of minerals such as Fe, Na and Mg which are essential for the normal functioning of the body, could well mean the immune booster can be taken as dietary supplement.